Mechanism research of PI3K/AKT pathway regulating PHF19 gene expression in prostate cancer - MING Daojing; GUO Mengmeng; ZHANG Jinhui; LIU Mengyang; SHI Minghui; LIU Shuyan; YUAN Shuai; ZENG Xiantao (Yixue xinzhi zazhi)
Objective To investigate the regulatory effect of the PI3K/AKT pathway on PHF19 gene expression in prostate cancer.Methods PC-3 cells were treated with the PI3K/AKT pathway inhibitor LY294002 or the activator EGF. Subsequently, the expression of TP63, ΔNp63 and PHF19 mRNA was detected using quantitative reverse transcription PCR (qRT-PCR). Potential transcription factors involved in PHF19 gene regulation were predicted using ChIPBase and JASPAR databases. The correlation between mRNA expressions of TP53, TP63 and PHF19 genes was analyzed through the GEPIA 2 database. Chromatin immunoprecipitation followed by quantitative PCR (ChIP-qPCR) was employed to assess the binding of ΔNP63 protein to the PHF19 gene promoter.Results LY294002 significantly reduced PHF19 mRNA expression (compared with different time treatment groups, P